P755 Inflammatory bowel disease and risk of Type 2 diabetes: a nationwide Danish cohort study 1977–2014. (25th January 2019) - Jess, T; Wang Jensen, B; Andersson, M; Villumsen, M; Højgaard Allin, K
Abstract: Background: The gut is a key regulator of glucose homeostasis, but the role of chronic intestinal inflammation in Type 2 diabetes (T2D) remains uncertain. We performed a Danish nationwide cohort study of the long-term risk of T2D in patients with inflammatory bowel disease (IBD). Methods: A total of 6, 028, 844 individuals, of whom 65, 180 were diagnosed with IBD, comprising Crohn's disease (CD) and ulcerative colitis (UC), during years 1977–2014, were followed until T2D, death, emigration, or December 31, 2014. The risk was presented as Standardised Incidence Ratios (SIR) with 95% confidence intervals (CI). Results: During 736, 072 person-years of follow-up, 3, 436 IBD patients developed T2D vs. 2, 224 expected (SIR, 1.54; 95% CI, 1.49-1.60). The risk was significantly increased both in patients with UC (SIR, 1.54; 95% CI, 1.48–1.60) and CD (SIR, 1.57; 95% CI, 1.47–1.67), and in women (SIR, 1.51; 95% CI, 1.44–1.59) and men (SIR, 1.57; 95% CI, 1.50–1.65). Although patients were most likely to receive a T2D diagnosis within the first year after IBD diagnosis (SIR, 4.48; 95% CI, 4.16–4.83), the risk remained elevated 20+ years following diagnosis (SIR, 1.26; 95% CI, 1.16–1.38) and was not explained by detection bias. Patients diagnosed with IBD during 2003–2014 (SIR, 1.79; 95% CI, 1.67–1.91) had significantly higher risk of T2D than patients diagnosed during 1977–1988 (SIR, 1.47; 95% CI, 1.39-1.56) and 1989–2002 (SIR, 1.48; 95% CI, 1.41–1.56) ( p < 0.01). Conclusions: This population-based cohort study shows an increased risk of T2D both in patients with UC and CD. Whether the significantly higher risk of T2D observed in recent years reflects an impact of current treatment options in IBD remains to be investigated.